Video-assisted thoracoscopic surgery lobectomy: pulled in many directions - Abdelsattar, Zaid M.; Blackmon, Shanda H. (Journal of Thoracic Disease, 2018)
In this issue of Journal of Thoracic Diseases, Liao and colleagues (1) describe with accompanying videos their technique of a fissureless, single direction video-assisted thoracoscopic surgery (VATS) left upper and left lower lobectomy. The authors report that this method is clear, easily followed, and can be applied to any lobectomy. The main concept of this technique is to maintain the same retraction on the lung, manage the most superficial structure first regardless of what it is, and proceed sequentially to deeper structures.